The variation of tobacco use behavior among Beijing college students and middle school students from 2008 to 2014 - Jia Li Duan; Xiao Peng Zeng; Ying Sun (Tobacco Induced Diseases, 2018)
Background Understanding the changes in smoking rate and try smoking rate among Beijing college students and middle school students from 2008 to 2014, and preliminarily evaluate the school tobacco control work efficiency.